The development of Means-Ends Analysis and Value Clarification Technique Integration Model to explore the local Wisdom in Historical Learning - Yudi Pratama; Sariyatun Sariyatun; Hermanu Joebagio (Journal of Education and Learning (EduLearn), 2017)
In fact, the differences exist is the true identity of the people of Indonesia making them rich of wisdom. The wisdom had by each group in each region (local wisdom) is one potential element which can be integrated in learning process to develop social solidarity, especially for the young. Accordingly, a suitable learning media in implementing such idea is needed to be considered. Therefore, this study was aimed to develop model Means-Ends Analysis and Value Clarification Technique as Integration media of Local Wisdom Values in History Learning to Increase Social Solidarity Thus, this study is designed to develop such media by using research and development model proposed by Dick and Carey. Based on the analysis results and findings, it can be concluded that Means-Ends Analysis model collaborated with Value Clarification Technique can help the students in identifying local wisdom values